Enhanced drug‐induced sleep endoscopy: Distinguishing central from obstructive apnea. (14th December 2022) - Cheong, Crystal S.; Dedhia, Raj C.; Seay, Everett G.; Jara, Sebastian M.; Mora, Jorge I.; Thaler, Erica R.; Schwartz, Alan R.
Abstract : This case report describes a patient originally diagnosed with obstructive sleep apnea (OSA) who was later found to have central sleep apnea (CSA) during drug‐induced sleep endoscopy, which was subsequently confirmed on an in‐laboratory sleep study. The revised diagnosis resulted in a change in recommended therapy from hypoglossal nerve stimulation to phrenic nerve stimulation. This case report is a reminder that the sleep surgeon must be cognizant of the possibility of CSA being misclassified as OSA especially as home sleep studies become increasingly routine, and discusses ways to more easily distinguish between CSA and OSA. Laryngoscope, 133:706–708, 2023